METHODS OF INVESTIGATION OF CHRONIC LIP CRACK - Shakirova , Fotima Abdulazizovna; Xudayberganova , Maftuna Xasan qizi (Innovative Development in Educational Activities, 2023)
To date, numerous methods for the diagnosis and treatment of chronic lip fissures have been presented, including schemes for both general and local treatment. However, the number of patients with this pathology tends to constantly grow, so the search for new drugs and methods for its treatment is important and justified. The article presents a clinical case of local treatment of a chronic lip fissure with the inclusion of a blockade with a local anesthetic and the application of a collagen-containing preparation in the treatment regimen, which showed a good clinical result.